Influence of NaOH Concentration on the Crystallization and Phase Development of Titanium Dioxide Derived from Titanium Slag via Hydrothermal Processing - Ngon, Hoang Trung; Tuan, Phan Dinh; Kien, Kieu Do Trung; Khoa, Tran Anh; Vi, Truong Khanh; Tuyet, Vo Ngoc (Indonesian Journal of Chemistry, 2025)
The hydrothermal method presents a promising approach for synthesizing high-quality rutile TiO2 pigments from titanium slag, utilizing controlled NaOH concentrations to modulate crystalline and morphological properties. This study examined the effects of varying NaOH concentrations on the crystallization and phase composition of TiO2 derived from titanium slag. Mixtures of titanium slag and NaOH underwent hydrothermal treatment at 200 °C for 18 h, and the resulting TiO2 samples were characterized using X-ray diffraction and scanning electron microscopy to evaluate phase composition and morphology. The results indicated that NaOH concentrations below 600 g/L promoted the formation of well-ordered, highly crystalline TiO2 with uniform crystal sizes. Conversely, higher NaOH concentrations increased the proportions of rutile and anatase phases, underscoring the significant impact of NaOH concentration on phase development. This study emphasizes the potential of the hydrothermal method in fine-tuning the properties of TiO2 for optimized pigment applications through adjustments in NaOH concentration.